Oxidation Resistance of Double-Layer MoSi2–Borosilicate Glass Coating on Fiber-Reinforced C/SiO2 Aerogel Composite - Dai, Tao; Song, Zihao; Du, Yuxuan; Zhao, Yifan; Cui, Sheng (Frontiers in Materials, 2021)
A MoSi2-borosilicate glass coating with high emissivity and oxidation resistance was prepared on the surface of fiber reinforced C/SiO2 aerogel composite by slurry method combined with embedding sintering method under the micro-oxygen atmosphere. Microstructure and phase composition of the coatings with different MoSi2 content before and after static oxidation were investigated. This composite material has both excellent radiating properties and outstanding oxidation resistance. The total emissivity values of the as-prepared coatings are all above 0.8450 in the wavelength of 300~2500 nm. Meanwhile, the as-prepared M40 coating also has superior thermal endurance after the isothermal oxidation of 1200 °C for 180 min with only 0.27% weight loss, which is contributed to the appropriate viscosity of the binder to relieve thermal stress defects. This material has broad application prospects in thermal protection.